Ablative fractional CO2 laser surgery improving sleep quality, pain and pruritus in adult hypertrophic scar patients: a prospective cohort study. Issue 1 (27th July 2021) - Lv, Kaiyang; Liu, Huazhen; Xu, Haiting; Wang, Caixia; Zhu, Shihui; Lou, Xiaozhen; Luo, Pengfei; Xiao, Shichu; Xia, Zhaofan
Abstract: Background: Poor sleep quality is associated with a decrease in quality of life in patients with major burn scars, combined with pruritus and pain. Few interventions have been reported to improve the sleep quality of patients with scars. In the current prospective cohort study, we investigated the efficacy of CO2 -ablative fractional laser (AFL) surgery vs conventional surgery in post-burn patients with hypertrophic scars with sleep quality as the primary study outcome. Methods: In total 68 consecutive patients undergoing scar surgical treatment were recruited, including a CO2 -AFL surgery cohort ( n = 35) and a conventional surgery cohort ( n = 33). A subgroup from the AFL cohort was selected. Sleep quality, pain and pruritus were evaluated. Multiple linear regression analyses were performed to reveal the effect of CO2 -AFL surgery. Results: The CO2 -AFL surgery cohort had significantly lower Pittsburgh sleep quality index (PSQI) global scores than the conventional surgery cohort after the last surgical treatment. In the subgroup of patients receiving hardware sleep monitoring, CO2 -AFL markedly increased deep sleep time, deep sleep efficiency and reduced initial sleep latency. Compared to the conventional surgery cohort, the CO2 -AFL cohort presented significantly lower pain and pruritus scores. Correlation analysis showed pain and pruritus were significantly associated with PSQI scores, and there were also significant correlations between pain and pruritus scores. Multiple linear regression analysis showed that surgery method was negatively linearly correlated with visual analog scale (VAS) pain score, brief pain inventory (BPI) total, VAS pruritus score, 5-D itch scale total, four-item itch questionnaire (FIIQ) total and PSQI total. Conclusions: CO2 -AFL surgery significantly improved sleep quality and reduced pain and pruritus of hypertrophic scar patients. The alleviation of sleep disorder was associated with improvement of deep sleep quality including deep sleep time and deep sleep deficiency. Trial registration: The Chinese Clinical Trial Registry (ChiCTR200035268) approved retrospectively registration on 5 Aug 2020.